Zgodnji Jurčič kot 'zapisovalec' in večerničar - Kmecl, Matjaž (Slavistična revija, 2006)
The article is a chapter from a monograph about the founder of the contemporary Slovene narrative prose Josip Jurčič. It mainly touches upon his initial "recording" of folk tales. It attempts to isolate the specific features of this activity and to define the transition to authorial narration.
Keywords: folk narrative; Jurčič, Josip; ljudska pripoved; recording; rural popular literature; Slovene literature; Slovene prose; slovenska književnost; slovenska proza; večernice; zapisovanje